Kinetic study on epoxy bisphenol-A diacrylate IPN formation - Lin, MS; Wang, MW (My University, 1999)
Interpenetrating polymer networks (IPN) based on diglycidyl ether of bisphenol-A (DGEBA) and bishenol-A diacrylate (BADA) in weight ratios of 100/0, 50/50, and 0/100 were blended and were cured simultaneously by using benzoyl peroxide (BPO) and 4,4'-methylenedianiline (MDA) as curing agents. Kinetic study during IPN formation was carried out at 65, 70, 75 and 80 degrees C. Absorbance changes at 1623.3 cm(-1) and 914 cm(-1) relating to concentration changes of C=C and epoxide were monitored with Fourier-transform infrared spectroscopy (FTIR). The epoxide cure kinetic data revealed a combination of non-catalytic bimolecular reaction and a catalyzed termolecular reaction, while the C=C cure kinetic data fitted a first-order reaction. The calculated kinetic parameters indicated decreased rate constants and increased activation energies of the IPN compared with those of the individual components. Presumably, chain entanglements between the two networks provide a sterically hindered environment for the cure reactions and vitrification restrains the chain mobility, accounting for the kinetic parameters. (C) 1999 Society of Chemical Industry.
Keywords: IPN; kinetics; decreased rate constants; increased activation energy